Epidemiology and Serum Metabolic Characteristics of Acute Myocardial Infarction Patients in Chest Pain Centers - Dazhi DENG; Ling LIU; Guangma XU; Jianting GAN; Yin SHEN; Ying SHI; Ruikai ZHU; Yingzhong LIN (Tehran University of Medical Sciences, 2018)
Background: We aimed to find a potential earlier diagnostic strategy for acute myocardial infarction (AMI) by investigating the epidemiology and serum metabolic characteristics of AMI patients in comparison with those of chest pain controls (CPCS). Methods: We conducted this prospective, non-randomized, observational study of patients with acute chest pain symptoms presenting to the Emergency Rooms (ER) in The People's Hospital of Guangxi Zhuang Autonomous Region, Nanning, Guangxi Province, China from January 2015 to July 2016. We included a cohort of 45 patients with AMI together with 45 age- and sex-matched CPCS. The epidemiology of AMI was collected, and the phenotypic characteristics of the serum metabolite composition of AMI patients were determined using a combination of 1H nuclear magnetic resonance (NMR)-based metabolomics and clinical assays. Results: The epidemiology showed that elderly AMI patients with chest pain syndrome presenting to ER have little awareness of their physical condition and compliance with medication. Signiﬁcant serum metabolic differences observed between AMI patients and CPCS were highlighted by system differentiations in multiple metabolic pathways including anaerobic glycolysis, gluconeogenesis, tricarboxylic acid cycle (TCA cycle), protein biosynthesis, lipoprotein changes, choline and fatty acid metabolisms and intestinal microbial metabolism. Conclusion: The epidemiology and serum metabolic phenotypes observed here demonstrated that integration of metabolomics with other techniques could be useful for better understanding the biochemistry of AMI and for potential AMI molecular diagnosis. We should improve the general public's awareness of AMI, including early symptoms, risk factors, emergency responses, and treatments for related comorbidities.